Sum Rate Maximization Based on Mobile User Clustering Assisted Downlink H-NOMA in 4-Tier B5G HetNet - Ghafoor, Umar; Siddiqui, Adil Masood; Khan, Humayun Zubair; Ali, Mudassar (2023 International Conference on Communication Technologies (ComTech), 2023)
A novel mobile user clustering (MUC) based downlink (DL) hybrid-nonorthogonal multiple access (H-NOMA) technique in 4-tier beyond fifth-generation (B5G) heterogeneous network (HetNet) is proposed for sum-rate maximization. We have formulated a sum-rate maximization problem based on the proposed technique subject to performance indicators (PIs). The considered PIs are the admission of mobile users (MUs) in clusters, the association of MUs with one of the base stations (BSs), allocation of power to the MUs, and MU's minimum rate requirement. This novel problem is solved to find an ∊-optimal solution within ∊ = 10 −3 using the outer approximation algorithm (OAA). We have compared the performance of the proposed technique for 4-tier HetNet, and existing 2-tier HetNet, macro BS-only (MBS-only) network. Simulation results ensure best performance of the proposed technique in 4-tier HetNet for sum rate maximization regarding PIs. It is shown through results that the proposed technique performs better in 4-tier HetNet than in existing 2-tier HetNet and MBS-only network regarding PIs.